Burden of cardiovascular disease attributable to dietary lead exposure among adults in China, 2017 - Yi-ling LI; Yi-zhong YAN; Jia-lin LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the burden of cardiovascular disease (CVD) attributable to dietary lead among Chinese adults aged 18 years and over in 2017, and to provide a reference for assessing health hazards caused by exposure to lead in diet. MethodsThe data on disease burden of CVD among residents in China were extracted from the Global Burden of Disease Study 2017 (GBD 2017). The information relevant to blood lead (BLL), bioavailability of lead ingestion through digestive tract and respiratory tract for Chinese adults and lead concentrations in food, air, and drinking water were retrieved form literatures published from January 2000 to July 2020 via searching PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), WanFang Database, and China Biology Medicine Database (CBMdisc). Population attribution fraction (PAF) was calculated using comparative risk assessment to estimate the burden of cardiovascular disease due to lead exposure. Based on the principle of integrated exposure uptake biokinetic (IEUBK) model, the contribution rate of dietary lead exposure to BLL was evaluated. ResultsThe pooled mean BLL for Chinese adults was 5.23 μg/dL (5.96 μg/dL for males and 4.90 μg/dL for females). In 2017, the total disability-adjusted life years (DALYs) of cardiovascular disease attributable to lead exposure in Chinese adults was 3.2396 million years and the standardized attributable DALY rate was high for the adults in Sichuan, Yunnan, and Hunan province, resulting in the loss of 635.00, 633.62, and 547.36 healthy life years per 100 000 people, respectively. The dietary lead was a major contributor to the adults' lead exposure, accounting for 57.01% and 58.60% of total lead exposure in male and female adults. The DALYs of cardiovascular disease attributed to dietary lead exposure was 1.8634 million, including 602.3 thousand DALYs of ischemic heart disease, 997.0 thousand DALYs of stroke, and 193.7 thousand DALYs of hypertensive heart disease. Conclusion For Chinese adults in 2017, lead exposure contributes to a significant ratio of burden of cardiovascular disease, and diet is a primary source of lead exposure.